Spinocerebellar ataxia type 11 (SCA11) is an uncommon cause of dominant ataxia among French and German kindreds. Issue 11 (28th July 2010) - Bauer, Peter; Stevanin, Giovanni; Beetz, Christian; Synofzik, Matthis; Schmitz-Hübsch, Tanja; Wüllner, Ullrich; Berthier, Eric; Ollagnon-Roman, Elisabeth; Riess, Olaf; Forlani, Sylvie; Mundwiller, Emeline; Durr, Alexandra; et al.
Abstract : Background: At least 28 loci have been linked to autosomal dominant spinocerebellar ataxia (ADCA). Causative genes have been cloned for 10 nucleotide repeat expansions (SCA1, 2, 3, 6, 7, 8, 10, 12, 17 and 31) and six genes with classical mutations (SCA5, 13, 14, 15/16, 27 and 28). Recently, a large British pedigree linked to SCA11 has been reported to carry a mutation in the TTBK2 gene. In order to assess the prevalence and phenotypic spectrum of SCA11, the authors screened 148 index patients of predominantly German (n=69) and French (n=79) descent with ADCA tested negative for a panel of SCA mutations (SCA1, 2, 3, 6, 7 and 17), for mutations in TTBK2 . Methods: In the German ADCA cohort, the complete coding sequence of the TTBK2 gene was PCR-amplified and screened for mutations by high-resolution-melting (HRM) analysis. In the French cohort, exons known to carry mutations were directly sequenced. For both cohorts, the gene-dosage alterations were assessed using a customised multiplex ligation probe amplification (MLPA) assay. Results: In two of 148 ADCA families—one German and one French—the authors identified a potentially disease-causing SCA11 mutation. Interestingly, both carried an identical two-basepair deletion (c.1306_1307delGA, p.D435fs448X in exon 12) leading to a premature stop codon. Gene-dosage alterations were not detected in the TTBK2 gene. Clinically, the SCA11 patients had phenotypic characteristics as described before presenting with slowly progressive almost pure cerebellar ataxia with normal life expectancy. Conclusion: SCA11 presented as ADCA III according to Harding's classification and is a rare cause of spinocerebellar ataxia in Caucasians accounting for less than 1% of dominant ataxias in central Europe.